2016
DOI: 10.1080/10409289.2016.1156989
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Preschool Activities: Exploring Outdoor Play

Abstract: Research Findings Outdoor play is important for children’s health and development, yet many preschool-aged children in childcare settings do not receive the recommended 60 minutes/day of outdoor play. Childcare providers have previously described parent-related barriers to increasing outdoor playtime, including parents not providing appropriate clothing for their children and parents’ preference for academics over active play. This study explored parent perceptions and knowledge of outdoor playtime in childcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
2
21
0
2
Order By: Relevance
“…With only 2% of parents agreeing with the idea that physical activity takes away time from learning opportunities, there may be greater than previously expected parental support for strategies to increase active playtime. A previous study found, however, that almost 80% of preschooler's parents reported no dialogue around the topic of outdoor play with their childcare provider (Jayasuriya et al 2016). These findings highlight the need to increase communication around and support of physical activity from all of the adults with whom young children interact.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…With only 2% of parents agreeing with the idea that physical activity takes away time from learning opportunities, there may be greater than previously expected parental support for strategies to increase active playtime. A previous study found, however, that almost 80% of preschooler's parents reported no dialogue around the topic of outdoor play with their childcare provider (Jayasuriya et al 2016). These findings highlight the need to increase communication around and support of physical activity from all of the adults with whom young children interact.…”
mentioning
confidence: 72%
“…A previous study found, however, that almost 80% of preschooler's parents reported no dialogue around the topic of outdoor play with their childcare provider (Jayasuriya et al . ). These findings highlight the need to increase communication around and support of physical activity from all of the adults with whom young children interact.…”
Section: Discussionmentioning
confidence: 97%
“…A aceitação e envolvimento das famílias nas práticas pedagógicas no exterior afigurase como um fator determinante no processo de transformação. Frequentemente, são referidos entraves colocados pelas famílias perante situações de roupas sujas, joelhos arranhados ou outras mazelas, constipações, etc., optando-se, assim, pela permanência no interior das salas, onde os profissionais se sentem mais seguros e em controlo da situação (Bento, 2017;Jayasuriya, Williams, Edwards, & Tandon, 2016).…”
Section: E N Vo LV I M E N T O Das Fa M í L Iasunclassified
“…Contradizendo as expectativas iniciais, as famílias apreciaram o investimento no brincar no exterior e colaboraram nas próprias transformações físicas dos espaços. Tal como é relatado noutros estudos (Jayasuriya et al, 2016;Vandermaas-Peeler, Dean, Biehl, & Mellman, 2019), o apoio das famílias em relação ao brincar no espaço exterior deve ser abordado, respeitando valores socioculturais, expectativas e prioridades dos pais em relação ao contexto educativo. A partilha e discussão destas dimensões entre famílias e profissionais poderá facilitar a adesão às iniciativas de promoção de experiências de brincar ao ar livre, sendo crucial que os pais sejam compreendidos como aliados no processo educativo e não como obstáculos para a concretização das intenções pedagógicas dos profissionais.…”
Section: R E C U R S O S E E Q U I Pa M E N T O Sunclassified
“…Findings from systematic reviews and randomised trials indicate that providing opportunities for active play during childcare can result in improvements in child physical activity levels . For example, modifying the scheduling of physical activity opportunities to provide children with more frequent opportunities for outdoor free play has been demonstrated to increase the level of overall child physical activity in care . In addition, a systematic review of the physical activity levels of children during indoor and outdoor play periods at childcare found that children spent almost half (48% [33%‐55%]) of their outdoor play time engaging in physical activity, compared to less than 10% of indoor play time being active .…”
Section: Introductionmentioning
confidence: 99%